Aglomerados de CayFe12-yO19(0 ≤ y ≤ 1,0) diluídos em uma matriz antiferromagnética - Passos, José Cleverton da Conceição (2015)
In this dissertation were studied powders and pellets of the CayFe12-yO19-aFe2O3(0 ≤ y ≤ 1,0) obtained by the proteic sol-gel process having as precursor coconut water. Samples were analyzed by techniques of X-ray diffraction, magnetometry and impedance. The impedance analysis showed that resistivity increased with the calcium concentration to 0.0 <y ≤ 0.2, but decreased for y> 0.2 and reached saturation at 7.5×106 Ω.cm to y = 0.9. The magnetization curve as a function of the magnetic field presents high values of saturation magnetization (Ms = 40 emu / g) with low remanent field (Mr = 6.7 emu / g) and coercive field (Hc = 320 Oe). By means of X- ray diffraction we have observed that agglomerates of the type hexaferrite CaM were formed after the doping with hematite, i.e., there was the existence of the two phases occurring antiferromagnetic coupling confirmed by exchange bias field of 9.6 Oe.